Predict clinical metabolic abnormalities by waist to height ratio depends on the measuring site. (Revista Venezolana de Salud Pública, 2020)
Aim: To determine the ability of the waist to height ratio to predict two or more clinical – metabolic disorders, according to site measuring of waist circumference. Methods: A cross-sectional analytical observational study was made. 800 adolescents, between 15 and 19 years old, of both sexes (405 men), enrolled in 31 institutions of secondary and university education of Iribarren Municipality - Lara – Venezuela were studied. Adolescents signed an informed consent. Socioeconomic status, dietary habits, physical activity, height and waist circumference at three anatomical sites: above the iliac crests, midpoint of abdomen and below costal margin were assessed. Waist to height ratio for each site was calculated. Next, blood pressure, serum glucose and serum lipids were evaluated. Bivariate statistical analysis and logistic regression were performed. Results: It was possible to model the presence of two or more clinical – metabolic disorders as a function of the waist to height ratio, both below the costal margin and above the iliac crests. However, the degree of association varied according to anatomical site, with a higher probability of two or more clinical disorders - metabolic in the first site. Such probability was directly proportional to the waist to height ratio and higher in men. Conclusion: Upper abdominal fat predicted better two or more clinical – metabolic disorders compared to the lower abdominal fat. Given these results, it could unify the anatomic site to measure of waist circumference, just below the costal margin, to identify adolescents with higher probability for such disorders, as risk factors for cardiovascular disease.
Keywords: Waist to height ratio; prediction; hypertension; dyslipidemias; hyperglycemia